Families with young children in: Footprints in Time the Longitudinal Study of Indigenous Children - Skelton, F; Atkinson, J; Hidderley, L (My University, 2011)
My baby likes ... going for walks, reading books, bath time, sleeping, drinking breast milk (ngunga milk), teasing, swearing, pulling out hair, splashing in his swimming pool. In 2008, more than 1,600 Aboriginal and Torres Strait Islander families were interviewed for Wave 1 of Footprints in Time: the Longitudinal Study of Indigenous Children. Families with children around one year old and families with children around four years old were chosen to take part in the study within 11 sites across Australian in remote, regional and urban areas. Families were interviewed for Wave 2 in 2009 when the children were around two and five years old, and are being interviewed again in 2010 for Wave 3. This session will introduce the study design and scope and highlight family characteristics such as family composition and size, age of mothers and number of siblings. There will be a brief analysis of family strengths, as reported through the study, major life events affecting families and parenting, and an examination of activities that are done with different members of the family. Some preliminary data from the Wave 2 Footprints in Time dataset, expected to be released late in 2010, will also be presented.
Keywords: Culture -- Indigenous; Surveys and Survey Methodology; Culture; Children; Surveys and Survey Methodology; Culture and language; Surveys and Survey Methodology; Children; Culture; Indigenous; Culture and identity; Culture, identity and language